Problems and Solutions in Improving Subsea Pipeline Competency and Quality: A Comprehensive Literature Review - Aung Ye Kyew (Collaborate Engineering Daily Book Series, 2023)
Subsea pipelines are an important means of transporting oil and gas offshore. However, subsea pipelines also face various problems that can reduce their competence and quality, such as corrosion, leaks, free span, and structural failure. This research aims to review literature related to problems and solutions in improving the competence and quality of underwater pipelines. The method used is a systematic review using the Scopus, Web of Science, and Google Scholar databases. The research results show that several solutions have been developed by researchers, such as using corrosion-resistant materials, installing support structures, covering bionic water plants, and self-necking plates. This research also identified several gaps and challenges that still need further research, such as the development of leak detection methods that are more accurate, efficient, and environmentally friendly, as well as optimizing the design and installation of subsea pipes to suit diverse marine environmental conditions.